Dividend Decisions and Long-Term Returns. The Case of the Polish Stock Market - Konieczka, Przemysław (Journal of Finance and Financial Law, 2023)
The purpose of the article. The purpose of the article was to examine how dividend decisions made by general shareholder meetings affect the stock price of public companies in Poland over the long term. Methodology. The study analyzed the impact of dividend decisions on the long-term patterns of stock returns using the buy-and-hold abnormal returns approach. In addition, the role of the dividend yield ratio in the formation of cross-sectional return volatility was examined. The conducted study referred to public companies listed on the main market of the Warsaw Stock Exchange. Results of the research. The results of the research can be summarized as follows. Firstly, the conducted empirical study showed the possibility of achieving abnormal returns on investments in portfolios composed of shares of dividend companies. The results showed the positive impact of dividend decisions on valuations of public companies in the long term. Stock portfolios of companies initiating and resuming dividend payments allow for obtaining positive abnormal returns over the long term, however, the returns achieved are statistically significant only for selected periods of stock holding. Secondly, the empirical study of cross-sectional returns showed possibility of achieving in the long term excess returns on shares of public companies with high dividend yields. The results achieved are in line with the results of research conducted for developed stock markets. The articel extends the considerations carried out for the Polish stock market in terms of the impact of dividend decisions on stock returns by including a long period in the analysis.